Analysis of the Influence Organizational Control System and Trust on Employee Performance - Salehan Salehan; Don Gusti Rao; Irzan Soepriyadi; Arief Nuryana; Yulius Luturmas (Budapest International Research and Critics University, 2022)
This study explores the relationship between organizational trust, output control, process control, normative control, and control on employee performance and organizational citizenship behavior (OCB). As part of the data gathering procedure utilizing the snowball sampling methodology, questionnaires were handed to bank workers based in Batam. This study collected data from 152 employees, and SPSS was used to assess the hypotheses. The findings of this study support the notion that trust has a significant and positive relationship with organizational confidence and employee performance, that output control has a substantial and positive relationship with OCB, that process control has no effect on OCB, that normative power has a significant and positive relationship with OCB, and that trust has a significant impact.